Use of Negative Pressure Wound Therapy With Automated, Volumetric Instillation for the Treatment of Extremity and Trunk Wounds: Clinical Outcomes and Potential Cost-Effectiveness - Gabriel, Allen (Eplasty, 2014)
Objective: A growing body of literature supports use of negative pressure wound therapy (NPWT) with instillation and dwell time (NPWTi-d) with positive clinical outcomes and potential cost savings. A retrospective analysis was performed to compare clinical outcomes of wounds treated with NPWTi-d versus NPWT and to estimate cost-differences between treatments based on clinical outcomes. Methods: Data were extracted from records of patients with extremity or trunk wounds treated with NPWT (n = 34) or NPWTi-d using saline or polyhexanide (n = 48). On the basis of outcomes data, a hypothetical economic model using cost assumptions was created to calculate cost savings for NPWTi-d (related to) number of debridements and length of therapy. Operating room debridement cost was $3393 according to Granick et al. Daily therapy cost for each modality was $194.80 (NPWTi-d) and $106.08 (NPWT) based on internal company information. Results: Results showed significant differences (P < 0.0001) between NPWTi-d and NPWT patients, respectively, for the following: mean operating room debridements (2.0 vs 4.4), mean hospital stay (8.1 vs 27.4 days), mean length of therapy (4.1 vs 20.9 days), and mean time to wound closure (4.1 vs 20.9 days). Hypothetical economic model showed potential average reduction of $8143 for operating room debridements between NPWTi-d ($6786) and NPWT ($14,929) patients. There was a $1418 difference in average therapy costs between groups ($799/NPWTi-d vs $2217/NPWT). Conclusions: In this study, NPWTi-d appeared to assist in wound cleansing and exudate removal, which may have allowed for earlier wound closure compared to NPWT. Hypothetical economic model findings illustrate potential cost-effectiveness of NPWTi-d compared to NPWT.